The Effect of The Jigsaw Learning Model on the Narrative Text Reading Comprehension Skills of V Grade Student at SDN 03 Buwaran Jepara: Pengaruh Model Pembelajaran Jigsaw terhadap Kemampuan Membaca Pemahaman Teks Narasi Siswa Kelas V SDN 03 Buwaran Jepara - Firnanda, Dina Aulia; Munir, Muhammad Misbahul (Madrosatuna: Journal of Islamic Elementary School, 2025)
This study aims to analyze the effect of the Jigsaw learning model on the reading comprehension ability of narrative texts among fifth-grade students at SDN 03 Buwaran Jepara. The research employed a quantitative method with a Pre-Experimental One Group Pretest-Posttest design, involving 25 students selected using a saturated sampling technique. Data were collected through multiple-choice test sheets that had been verified for validity and reliability. The findings revealed a significant improvement in reading comprehension after the application of the Jigsaw learning model, with an average pretest score of 56.80 and a posttest score of 77.20. The Paired Samples T-test produced a t-value of 11.185, greater than the t-table value of 2.064, with a significance level of < 0.001, indicating a significant difference before and after the implementation of the model. Furthermore, Anova analysis showed a contribution of 66.8%, reinforcing the positive impact of the Jigsaw learning model. Therefore, it can be concluded that the Jigsaw learning model significantly enhances students’ ability to comprehend narrative texts.